Awareness of the Benefits of Strategic Planning For Educational Institutions - Rachmad, Ferizal (Basecamp Economics PubMed, 2023)
This article aims to determine the benefits of strategic planning for Islamic educational institutions. The method used is a literature review, by collecting various supporting article references from national journals. The results of this study explain, if strategic planning can be made and implemented correctly and supported by leadership commitment, then strategic planning can provide benefits for Islamic educational institutions, including: (1) Strategic planning can strengthen the